Uncertainty and capacity constraints: Reconsidering the aggregate production function - Eduard Gracia (Economics: The Open-Access, Open-Assessment E-Journal, 2011)
The CobbDouglas function is today one of the most widely adopted assumptions in economic modeling, yet both its theoretical and empirical bases have long been under question. This paper builds an alternative function on very different (albeit also neoclassical) microfoundations aimed at both addressing those theoretical drawbacks and providing a better empirical fit than the CobbDouglas formula. The new model, unlike the CobbDouglas function, does not portray installed capacity as aggregate capital but as a sunk cost generating economic rents. An analysis of 1949-2008 annual U.S. growth data suggest this alternative model explains nearly 85 percent of GDP fluctuations and is empirically more robust than the CobbDouglas, whilst both contemporary and lagged aggregate capital are statistically rejected as explanatory variables. This lends support to the old Cambridge Critique”, according to which using value-weighted capital aggregates to explain production simply makes no sense. At face value, these results not only pose a question on any macroeconomic model assuming a CobbDouglas function but also point towards an alternative interpretation of phenomena such as the way monetary policy impacts productivity.
Keywords: E22; E23; 330; production function; CobbDouglas; capital controversy; Produktionsfunktion; Mikroökonomische Fundierung; Cobb-Douglas-Produktionsfunktion; Kapitaltheorie; Schätzung; Sozialprodukt; USA